H3K4 Methylation Regulates LPS-Induced Proinflammatory Cytokine Expression and Release in Macrophages. Issue 3 (March 2019) - Zhao, Shuqi; Zhong, Yuyun; Fu, Xiaoxia; Wang, Yiqian; Ye, Ping; Cai, Junwei; Liu, Yun; Sun, Jiang; Mei, Zhuzhong; Jiang, Yong; Liu, Jinghua
Abstract : ABSTRACT: Histone methylation is an important epigenetic mechanism that plays an essential role in regulating gene expression in mammalian cells. To understand its influence on inflammation, methylation of H3K4, H3K9, H3K36, H3K79, and H4K20, the most common histones methylated in the inflammatory response was analyzed in murine RAW264.7 cells and bone marrow-derived macrophages (BMDMs) upon lipopolysaccharide (LPS) stimulation. LPS stimulation resulted in enhanced methylation at H3K4 and H3K9 in both RAW264.7 and BMDMs. To further confirm whether LPS-stimulated H3K4me2 and H3K9me2 were responsible for subsequent proinflammatory cytokine expression, the recruitment of H3K4me2 and H3K9me2 at the promoters of interleukin (IL)-6 and tumor necrosis factor-α (TNF-α) was assessed. H3K4me2, but not H3K9me2, was enriched at the promoters of both IL-6 and TNF-α. Furthermore, LPS-stimulated gene expression and release of IL-6 and TNF-α were markedly suppressed in macrophages by MTA, a specific inhibitor of H3K4 methylation. These results demonstrate that histone methylation, in particular H3K4me2, plays a critical role in the regulation of LPS-induced expression and release of IL-6 and TNF-α.